Development Of Flywheel Inverter System For Voltage Sag Mitigation - Ishak, Ruhaizad (2006)
Power quality is an issue that has been given a continuous attention by the electricity providers and also the consumers. Nowadays, the application of power electronic devices in the industrial sector has rapidly increased. Many of the equipment used in the industries are sensitive to an even small disturbance in power supply such as voltage sag. Voltage sag can cause low quality product, low production quantity and also machine restarting. The voltage sag problem can reduce the profit in long term if it is not given a proper attention.There are many type of solutions that have been developed to mitigate the voltage sag problem. The type of solution that is usually taken by the consumers is by installing energy storage device such as battery, capacitor and motor generator (MG) to inject the power back to the AC system during the voltage sag. In this work, a flywheel is used as the energy storage device. Flywheel has few advantages such as long life cycle, low maintenance work and also cheap. A DC machine has been used with the flywheel in this application. At normal condition, the flywheel stores kinetic energy during the rotation of the machine. The kinetic energy will be transformed to electrical energy when there is a sag in the AC system. In order to deliver the energy to the AC system, the flywheel is used with the static synchronous compensator (STATCOM) system. This system supplies reactive power to compensate the voltage loss during the sag. This work has been divided into two parts which are the simulation and the experiment part. Two types of faults which are balanced phase fault and unbalanced phase fault have been simulated. The balanced phase fault has been created by starting of large induction motor. On the other hand, the unbalanced phase fault has been created by performing a short circuit on the AC supply system. For the experiment part, this sag mitigation system has been tested under the balanced phase fault condition. From both the simulation and experiment results, a good agreement has been obtained. The mitigation system has shown a good ability in mitigating voltage sag problem.